EPCO-15. TUMOR TREATMENT WITH IONIZING RADIATION IS ASSOCIATED WITH A CLINICALLY RELEVANT DELETION SIGNATURE. (9th November 2020) - Kocakavuk, Emre; Anderson, Kevin; Johnson, Kevin; Varn, Frederick; Amin, Samirkumar; Barthel, Floris; Verhaak, Roel
Abstract: Diffuse gliomas are highly aggressive brain tumors that invariably relapse despite treatment with chemo- and radiotherapy. Treatment with alkylating chemotherapy can drive tumors to develop a hypermutator phenotype. In contrast, the genomic effects of radiation therapy (RT) remain unknown. We analyzed the mutational spectra following treatment with ionizing radiation in sequencing data from 190 paired primary-recurrent gliomas from the Glioma Longitudinal Analysis (GLASS) dataset and 2249 post-treatment metastatic tumors from the Hartwig Medical Foundation. We identified a significant increase in the frequency of small deletions following radiation therapy that was independent of other factors. These novel deletions demonstrated distinct characteristics when compared to pre-existing deletions present prior to RT-treatment and deletions in RT-untreated tumors. Radiation therapy-acquired deletions were characterized by a larger deletion size (GLASS and metastatic cohort, P = 1.2e-02 and P = 8e-11, respectively; Mann-Whitney U test), an increased distance to repetitive DNA elements ( P < 2.2e-16, Kolmogorov-Smirnov test) and a reduction in microhomology at breakpoints ( P = 3.2e-02, paired Wilcoxon signed-rank test). These observations suggested that canonical non-homologous end joining (c-NHEJ) was the preferred pathway for DNA double strand break repair of RT-induced DNA damage. Furthermore, radiotherapy resulted in frequent chromosomal deletions and significantly increased frequencies of CDKN2A homozygous deletions. Finally, a high burden of RT-associated deletions was associated with worse clinical outcomes (GLASS and metastatic cohort, P = 4.7e-02, HR = 2.59 [95% CI: 1.01, 6.60] and P = 2.5e-02, HR = 1.43 [95% CI: 1.05, 1.94], respectively; multivariable Cox regression), suggesting that effective repair of RT-induced DNA damage is detrimental to patient survival and that inhibiting c-NHEJ may be a viable strategy for improving the cancer-killing effect of radiotherapy. Taken together, the identified genomic scars as a result of radiation therapy reflect a more aggressive tumor with increased levels of resistance to follow up treatments.